EARLY URBANIZATION PROCESSES IN FERGANA VALLEY (based on archaeological materials) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the study of urbanization processes in the Ferghana Valley. Taking into account the city-forming factors, the authors distinguish three groups of archaeological sites. The first group is the first city (ilk shaharlar), the second group is the most ancient cities (eng kadimgi shaharlar), the third group is ancient cities (kadimgi shaharlar). Dalverzin settlement is considered to be the most ancient city of Ferghana.